2017
DOI: 10.1128/jb.00412-16
|View full text |Cite
|
Sign up to set email alerts
|

The Colicin E1 TolC Box: Identification of a Domain Required for Colicin E1 Cytotoxicity and TolC Binding

Abstract: Colicins are protein toxins made by Escherichia coli to kill related bacteria that compete for scarce resources. All colicins must cross the target cell outer membrane in order to reach their intracellular targets. Normally, the first step in the intoxication process is the tight binding of the colicin to an outer membrane receptor protein via its central receptor-binding domain. It is shown here that for one colicin, E1, that step, although it greatly increases the efficiency of killing, is not absolutely nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 48 publications
(62 reference statements)
7
23
0
Order By: Relevance
“…3 A ). This observation is notable in light of the fact that, in previous studies, similar peptides were shown to bind TolC (18, 20) and to occlude the channel, as reflected in diminished conductance (18, 19). These studies, however, did not investigate the effects of colicin E1 fragments on the efflux function of the pump.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…3 A ). This observation is notable in light of the fact that, in previous studies, similar peptides were shown to bind TolC (18, 20) and to occlude the channel, as reflected in diminished conductance (18, 19). These studies, however, did not investigate the effects of colicin E1 fragments on the efflux function of the pump.…”
Section: Resultssupporting
confidence: 51%
“…In particular, peptides including residues 100-120 of colicin E1 (termed the ‘TolC box’), with additional amino acids at the C-terminus of the ‘box’, have been shown to co-elute with TolC (18) and to disrupt channel conductance (19). A subsequent study confirmed the identity of the minimal T-domain segment that binds TolC, showing that E. coli exposure to peptides comprising residues 100–120 is sufficient to prevent subsequent binding of full-length colicin E1 (as reflected in the fact that the bacteria were protected from the colicin’s cytotoxic effects (20)). Notably, none of these studies investigated the effects of exposure to colicin E1 fragments on TolC’s efflux activity.…”
Section: Introductionmentioning
confidence: 85%
“…Another curious finding is the structural homology of AcrA to colicin E3 (Fig. 7a-c, RMSD = 0.85 Å), which interacts with BtuB (vitamin B12 receptor), a β-barrel OM protein similar to TolC 52,53 . We have used the colicin homology to suggest possible modes of AcrA binding to TolC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Over 20 colicins have been studied and the functional diversity of colicins offers unique cell-killing mechanisms ( 1 ). For example, colicins Ia ( 5 ) and E1 ( 6 ) form pores on the inner membrane, colicin M inhibits cell-wall biosynthesis by degrading an undecaprenyl phosphate-linked peptidoglycan precursor ( 7 ), colicin E2 degrades DNA templates ( 8 ) and colicin E3 degrades 16S ribosomal RNA resulting in slow translation ( 9 ). Therefore, colicins can target specific microbes by penetrating cells and disrupting cellular components.…”
Section: Introductionmentioning
confidence: 99%